Heidegger in the Islamicate world - Moser, Kata, 1981-; Gösken, Urs; Hayes, Josh (New Heidegger research., 2019)
This volume offers insights into a unique philosophical landscape and enriches current Heidegger studies by offering fresh perspectives on his philosophy that are based on the traditions of Arabic and Persian Islamic philosophy.